An appraisal of traditional knowledge of plant poisoning of livestock and its validation through acute toxicity assay in rats - Rasool, Faisal; Nizamani, Zaheer Ahmed; Ahmad, Khawaja Shafique; Parveen, Fahmida; Khan, Shahzad Akbar; Sabir, Naveed (Frontiers in Pharmacology, 2024)
Background: Kashmir Himalaya hosts the most diverse and rich flora in the world, which serves as grazing land for millions of small ruminants in the area. While most plant species are beneficial, some can be poisonous, causing economic losses and animal health issues for livestock. Consequently, this study is the first comprehensive report on the traditional phyto-toxicological knowledge in District Muzaffarabad and the assessment of its authenticity through experimental studies in rats. Methods: The data regarding traditional knowledge was gathered from 70 key respondents through semi-structured interviews, which was quantitatively analyzed and authenticated through plant extract testing on Wistar female rats and comparison with published resources. Results: A total of 46 poisonous plant species belonging to 23 families and 38 genera were reported to be poisonous in the study area. Results revealed that leaves were the most toxic plant parts (24 species, 52.1%), followed by the whole plant (18 species, 39.1%), stem (17 species, 36.9%), and seeds (10 species, 21.7%). At the organ level, liver as most susceptible affected by 13 species (28.2%), followed by the gastrointestinal tract (15 species, 32.6%), nervous system (13 species, 8.2%), dermis (8 species, 17.3%), renal (7 species, 15.2%), respiratory (4 species, 8.7%), cardiovascular system (3 species, 6.5%), and reproductive system (2 species, 4.3%). The poisonous plant species with high Relative frequency citation (RFC) and fidelity level (FL) were Nerium oleander (RFC, 0.6; FL, 100), Lantana camara (RFC, 0.6; FL, 100), and Ricinus communis (RFC, 0.6; FL, 100). Experimental assessment of acute toxicity assay in rats revealed that Nerium oleander was the most toxic plant with LD50 of (4,000 mg/kg), trailed by Ricinus communis (4,200 mg/kg), Lantana camara (4,500 mg/kg), and Datura stramonium (4,700 mg/kg); however, other plants showed moderate to mild toxicity. The major clinical observations were anorexia, piloerection, dyspnea, salivation, tachypnea, constipation, diarrhea, tremor, itchiness, and dullness. Conclusion: This study showed that numerous poisonous plants pose a significant risk to the livestock industry within Himalayan territory, leading to substantial economic losses. Consequently, it is of utmost importance to conduct further comprehensive studies on the phytotoxicity of plants.